Effects of Saccharomyces Cerevisiae Cultures on Performance and Immune Performance of Dairy Cows During Heat Stress - Du, Dewei; Feng, Lei; Chen, Peng; Jiang, Wenbo; Zhang, Yu; Liu, Wei; Zhai, Ruina; Hu, Zhiyong (Frontiers in Veterinary Science, 2022)
The dairy farming industry is facing massive economic losses as heat stress continues to rise. The purpose of this study was to see how feeding Saccharomyces cerevisiae culture (SC) influences productive performance, lactation performance, serum biochemical indexes, hormonal level, antioxidant capacity, and immune function in mid-lactating cows during heat stress. Forty-five healthy mid-lactation dairy cows with comparable milk yield, lactation days, and parity were randomly divided into 3 groups of 15 cows each. The control group (CON) was fed the basal diet, while the treatment groups were fed the basal diet + first Saccharomyces cerevisiae culture 100 g/d (SC-1) and the basal diet + second Saccharomyces cerevisiae culture 30 g/d (SC-2), respectively. The SC-1 and SC-2 groups with SC added in the treatment groups reduced rectal temperature and respiratory rate in heat-stressed cows (P<0.05). The milk yield of SC-1 and SC-2 treatment groups was significantly higher than that of CON (P<0.05). Except for somatic cell count, which was significantly lower in SC-1 and SC-2 than in CON (P<0.05), there were no significant differences in the milk components. The addition of SC: (i) increased serum urea levels (P<0.05), but there was no significant difference in glucose, total cholesterol, Alanine transaminase, Aspartate aminotransferase, total protein, albumin, and alkaline phosphatase levels (P>0.05); (ii) increased serum levels of immunoglobulin-A, immunoglobulin-G, immunoglobulin M, interleukin-4, interleukin-10, and heat shock protein-70 (P<0.05), while decreasing serum levels of interleukin-1β, interleukin-6, interleukin-2, interferon-γ, and tumor necrosis factor-α (P<0.05); (iii) increased total antioxidant capacity, glutathione peroxidase, and superoxide dismutase in serum (P<0.05), while decreasing malondialdehyde; (iv) increased serum levels of glucocorticoids, insulin, cortisol, and prolactin (P<0.05), while decreasing the serum levels of triiodothyronine and thyroxine (P<0.05). In conclusion, under the current experimental conditions, the addition of SC can reduce rectal temperature and respiratory rate in heat-stressed mid-lactation cows, reduce the number of somatic cells in milk and improve the mid-lactation cow performance. Also, SC addition to the diet can raise serum urea levels, regulate serum hormone levels, boost antioxidant capacity in mid-lactation cows, and boost overall immunity.